2020
DOI: 10.1186/s12939-020-01287-0
|View full text |Cite
|
Sign up to set email alerts
|

Unmet mental health needs in the general population: perspectives of Belgian health and social care professionals

Abstract: Background An unmet mental health need exists when someone has a mental health problem but doesn’t receive formal care, or when the care received is insufficient or inadequate. Epidemiological research has identified both structural and attitudinal barriers to care which lead to unmet mental health needs, but reviewed literature has shown gaps in qualitative research on unmet mental health needs. This study aimed to explore unmet mental health needs in the general population from the perspectiv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…System-level factors related to underfunding and a lack of trained professionals impede equitable access (Bartram, 2017; Coalition of Ontario Psychiatrists, 2018; Fleury & Grenier, 2012; Mental Health Commission of Canada, 2012, 2017). Individuals who, because of low income and/or lack of supplementary health insurance, cannot afford consultation in the private sector (Gulliver, Griffiths, & Christensen, 2010; Harvey & Gumport, 2015; Mojtabai, 2005; Perreault et al, 2013; Walker, Cummings, Hockenberry, & Druss, 2015) face long wait times for access to psychotherapy in the public sector (van Nieuwenhuyse & Dumas, 2012), leading to unmet need for care and increased first appointment nonattendance (Davis, Smith, Talbot, Eldridge, & Betts, 2020; Rens, Dom, Remmen, Michielsen, & Van Den Broeck, 2020; Sweeney et al, 2019). Economic evaluation of psychotherapy and CBT is needed to support decision making around the allocation of resources to overcome barriers to care for patients with anxiety disorders, which are among the most common (Kessler et al, 2005) and economically impactful (Chisholm et al, 2016) mental disorders globally.…”
Section: Introductionmentioning
confidence: 99%
“…System-level factors related to underfunding and a lack of trained professionals impede equitable access (Bartram, 2017; Coalition of Ontario Psychiatrists, 2018; Fleury & Grenier, 2012; Mental Health Commission of Canada, 2012, 2017). Individuals who, because of low income and/or lack of supplementary health insurance, cannot afford consultation in the private sector (Gulliver, Griffiths, & Christensen, 2010; Harvey & Gumport, 2015; Mojtabai, 2005; Perreault et al, 2013; Walker, Cummings, Hockenberry, & Druss, 2015) face long wait times for access to psychotherapy in the public sector (van Nieuwenhuyse & Dumas, 2012), leading to unmet need for care and increased first appointment nonattendance (Davis, Smith, Talbot, Eldridge, & Betts, 2020; Rens, Dom, Remmen, Michielsen, & Van Den Broeck, 2020; Sweeney et al, 2019). Economic evaluation of psychotherapy and CBT is needed to support decision making around the allocation of resources to overcome barriers to care for patients with anxiety disorders, which are among the most common (Kessler et al, 2005) and economically impactful (Chisholm et al, 2016) mental disorders globally.…”
Section: Introductionmentioning
confidence: 99%
“…This might explain the reported unmet need for discussing family planning in our study. Previous research has shown that mental health professionals considered taboo and stigma barriers to providing care for their patients [ 26 ]. For patients with a mental health disorder, complex care needs, care avoidance, and lack of trust in mental health professionals hindered patients from seeking help.…”
Section: Discussionmentioning
confidence: 99%
“…Occupational status contained the following categories: professionally active (worker, employee, self-employed, official), unemployed, unable to work, retired (or early retirement), student, housewife/man, career break, or other situation. Four age groups were distinguished: early adulthood (ages 18-34), early middle age (ages [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49], late middle age (ages 50-64), and late adulthood (ages 65 and older).…”
Section: Sociodemographic Characteristicsmentioning
confidence: 99%
“…Access to adequate mental health care services is one of those weaknesses. A study by Rens et al 48 highlighted the issue of unmet mental health needs in the general population in Belgium. Moreover, nearly half of the patients in Belgium had to wait one month or more for a first contact in 2017 49 .…”
Section: Practical Implications and Recommendationsmentioning
confidence: 99%